FACTORS RELATED TO ANXIETY IN HEMODIALYSIS PATIENTS IN MALANG CITY, INDONESIA - Zaqqi Ubaidillah; Anggraini Dwi Kurnia; Izzul Fiqri (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Objective: This study aimed to determine the factors associated with anxiety in hemodialysis patients. Methods: This study used a cross-sectional design. An accidental sampling technique was used to obtain a total sample of 34 respondents. The data were analyzed using Fisher’s exact test. Results: Based on the results of statistical tests, it is known that the level of anxiety related to hemodialysis patients, namely hemodialysis duration with Fisher's exact (P= 0.020). While the hemodialysis time value (P= 0.173, and work status value (P = 0.080), there was no association with the anxiety of hemodialysis patients. Conclusion: This study concluded that the duration of hemodialysis was related to the anxiety of hemodialysis patients, whereas there was no result in hemodialysis and occupational status related to the incidence of anxiety in hemodialysis patients. Therefore, healthcare providers should concern about the duration of hemodialysis time to prevent anxiety.